Secondary agency conflicts: A synthesis and proposed measurement model. Issue 5 (October 2018) - Sutton, Christine; Veliyath, Rajaram; Pieper, Torsten M.; Hair, Joseph F.; Caylor, Marcus
Abstract: Secondary agency conflicts typically arise when ownership and control are combined in the hands of dominant shareholders who could then seek to misappropriate returns at the expense of minority shareholders. This type of agency conflict has attracted attention from researchers for the past nearly three decades. However, efforts at measuring secondary agency conflicts have been fragmented and scattered. The absence of a coherent and valid approach to assess the scope and intensity of secondary agency conflicts has impeded progress in both empirical and conceptual development of the topic area. Based on a review of the extant body of literature, this paper develops a composite Shareholder Inequity index that measures the potential for secondary agency conflicts employing three different governance dimensions that are grounded in the agency literature: blockholder power, differential control, and the absence of board neutrality. The index is tested and validated empirically using a sample of 748 publicly listed U.S. firms. The resulting Shareholder Inequity index demonstrates high levels of validity and reliability. Future corporate governance studies can utilize this validated measure to investigate potential secondary agency conflicts more consistently and rigorously in order to strengthen organizational theory development and research.